PENGARUH DIGITAL MARKETING DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN MELALUI CITRA MEREK PADA UMKM DAPUR ARU OLAHAN KELOR KAMPAR - Aprilia, Aqsha; Safitri, Syofiatul (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine and analyze the effect of Digital marketing and Product Variety through Brand Image on Customer Purchase Decisions at UMKM Dapur Aru Olahan Kelor Kampar. There are 7 hypotheses in this study using a quantitative approach by distributing questionnaires to 96 respondents who are consumers of Dapur Aru Olahan Kelor Kampar customers. The research sample was taken using non-probability sampling method with purposive sampling technique, namely the criteria that have bought 2 times in Aru's Kitchen. This study uses an analysis method using PLS-SEM version 4. The results showed that digital marketing has no significant effect on customer purchasing decisions. Product Variety Variety has a significant effect on Customer Purchasing Decisions. Digital marketing has no significant effect on Brand Image. Product Variety has a significant effect on brand image. Brand image variables have a significant effect on customer purchasing decisions. Digital marketing variables have no significant effect on Customer Purchasing Decisions through Brand Image. Product Variety Variables have a significant effect on Customer Purchasing Decisions through Brand Image at UMKM Dapur Aru Olahan Kelor Kampar. Keywords: